2018
DOI: 10.1007/s00401-017-1804-9
|View full text |Cite
|
Sign up to set email alerts
|

BACE1 inhibition more effectively suppresses initiation than progression of β-amyloid pathology

Abstract: BACE1 is the rate-limiting protease in the production of synaptotoxic β-amyloid (Aβ) species and hence one of the prime drug targets for potential therapy of Alzheimer’s disease (AD). However, so far pharmacological BACE1 inhibition failed to rescue the cognitive decline in mild-to-moderate AD patients, which indicates that treatment at the symptomatic stage might be too late. In the current study, chronic in vivo two-photon microscopy was performed in a transgenic AD model to monitor the impact of pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 89 publications
(127 reference statements)
3
71
0
Order By: Relevance
“…We addressed the potential reason for the differential effect of tau deletion at different stages of Ab deposition. Interestingly, our data indicate that tau deletion effectively prevented the formation of satellite plaques, which are known to frequently form close to preexisting plaques (McCarter et al, 2013;Peters et al, 2018). Satellite plaque formation might result from enrichment of BACE1 and APP (Zhao et al, 2007) and thus potentiated Ab production (Sadleir et al, 2016) in plaque-associated axonal dystrophies.…”
Section: Discussionmentioning
confidence: 71%
“…We addressed the potential reason for the differential effect of tau deletion at different stages of Ab deposition. Interestingly, our data indicate that tau deletion effectively prevented the formation of satellite plaques, which are known to frequently form close to preexisting plaques (McCarter et al, 2013;Peters et al, 2018). Satellite plaque formation might result from enrichment of BACE1 and APP (Zhao et al, 2007) and thus potentiated Ab production (Sadleir et al, 2016) in plaque-associated axonal dystrophies.…”
Section: Discussionmentioning
confidence: 71%
“…1a-c). We started our recordings at the age of 4.5 months, which in this mouse model represents the early phase of A plaque deposition 26,27 . To characterize the cell identity of the imaged neurons, we performed post-hoc immunostainings and found that the vast majority (96.4 %) of GCaMP6s expressing cells was in fact excitatory (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 4a, week 0: 39.9µm, week 2: 36.8µm, week 4: 34.9 µm -plaque distance decreases as plaques grow over time 27,30,31 ), we divided neurons into close (<= 40 µm form the plaque border) and distant (> 40µm from plaque border) from the nearest plaque, respectively (of note, the effect is also true for other cut offs, such as 20, 60 or 80 µm). The fraction of highly or rarely active neurons did not differ significantly between close and distant neurons at the level of individual experiments (Suppl.…”
Section: Emergence and Fate Of Highly Active Cellsmentioning
confidence: 99%
“…Acetylcholinesterase inhibitors are efficacious in improving cognitive function of mild‐to‐moderate AD (Gault et al, ). And pharmacological β‐amyloid precursor cleavage enzyme inhibition has found slow progressive β‐amyloid deposition and associated synaptic pathology in a transgenic AD model (Peters et al, ). These may imply that glucuronidated curcumin may have little effect on cognition.…”
Section: Discussionmentioning
confidence: 99%